Transparansi Pengelolaan Dana Desa Tahun 2022 Di Desa Mondu Kecamatan Kanatang Kabupaten Sumba Timur Ditinjau Dari Peraturan Menteri Dalam Negeri Nomor 20 Tahun 2018 Tentang Pengelolaan Keuangan Desa - Ngana, Debi Ndai; Monteiro, Josef Mario; Tupen, Rafael Rape (Law Faculty, Nusa Cendana University, 2025)
This study investigates the level of transparency in the management of Village Funds in 2022 in Mondu Village, East Sumba Regency, by referring to Permendagri Number 20 of 2018. Using empirical legal research methods and socio-legal approaches, it was found that although important documents such as the APBDes and RKPDes exist, information is still difficult to access because it is only available in physical form (such as notice boards and manual archives) without a digital platform. The Accountability Letter (SPJ) for Village Funds is inaccessible to the general public, and reliance on manual systems hinders community participation, especially from vulnerable groups. The results of the study indicate a gap between compliance with administrative regulations and the principle of true transparency, which is further exacerbated by the lack of technological infrastructure, low public understanding of the APBDes, and lack of socialization and active involvement. Structural problems such as unstable internet connections and lack of computer access further exacerbate accountability problems. Recommendations from this study include accelerating the digitalization of documents, strengthening technology-based village information systems, and increasing community capacity through more intensive socialization. These changes in governance are expected to increase public trust and encourage more inclusive village development by following the principles of good governance.